Automatic analysis of corneal nerves imaged using in vivo confocal microscopy. (28th November 2017) - Kim, Juno; Markoulli, Maria
Abstract : Interest has grown over the past decade in using in vivo confocal microscopy to analyse the morphology of corneal nerves and their changes over time. Advances in computational modelling techniques have been applied to automate the estimation of sub‐basal nerve structure. These objective methods have the potential to quantify nerve density (and length), tortuosity, variations in nerve thickness, as well as temporal changes in nerve fibres such as migration patterns. Different approaches to automated nerve analysis, methods proposed and how they were validated in previous literature are reviewed. Improved understanding of these approaches and their limitations will help improve the diagnostic leverage of emerging developments for monitoring the onset and progression of a broad class of systemic diseases, including diabetes.